Structural integrity of MIH-affected teeth after treatment with fluoride varnish or resin infiltration: An 18-Month randomized clinical trial - Nogueira, Vinícius Krieger Costa [UNESP]; Mendes Soares, Igor Paulino [UNESP]; Fragelli, Camila Maria Bullio [UNESP]; Boldieri, Talita [UNESP]; Manton, David John; Bussaneli, Diego Girotto [UNESP]; Cordeiro, Rita de Cássia Loiola [UNESP] (Elsevier, 2021)
Objective: To evaluate the influence of fluoride varnish (FV) therapies or resin infiltration (RI) to maintain the structural integrity of Molar Incisor Hypomineralization (MIH) -affected teeth. Methods: Fifty-one children aged 6–12 years with at least one incisor and one first permanent molar with yellow/brown MIH opacities were included. Patients were randomly allocated into three groups: FV – Fluoride Varnish (Duraphat); FV+etch – Fluoride Varnish (Duraphat) after enamel etching with 37% phosphoric acid; or RI – Resin Infiltration system (Icon). Opacities were monitored for 18 months. The primary outcome was the loss of integrity due to post-eruptive enamel breakdown (PEB). Covariables included sex, age, DMFT index, opacity colour, plaque index, number of MIH-affected teeth, and number of MIH-affected surfaces. Fisher's Exact was used to test the association of treatments with PEB, the Kaplan-Meyer method analysed the survival rates and Cox-regression determined which covariables would predict failure (α=0.05). Results: From a total of 235 teeth, the PEB rate for RI (6.1%) was significantly lower (p<0.05) than FV (17.9%; OR 3.0, 95%CI 1.07, 8.48) and FV+etch (17.3%; OR 3.1, 95%CI 1.13, 8.73). DMFT index >3, brown opacities, cusp involvement, and age between 6–8 years predicted PEB (p<0.05). Conclusions: Resin infiltration positively influenced the structural integrity maintenance of MIH-affected teeth by decreasing the risk of enamel breakdown over18 months follow-up. Registry of Clinical Trials (RBR-8wwk3n). Clinical Relevance: Resin infiltration proved to be a more efficacious intervention to maintain the structural integrity of MIH-affected teeth than fluoride varnish therapies.
Keywords: Dental enamel; Enamel defects; Fluoride therapy; Icon; Molar incisor hypomineralization; Resin infiltration